Growth and energy and protein intake of preterm newborns in the first year of gestation-corrected age - Bernardi, Júlia Laura Delbue; Goulart, Ana Lúcia; Amancio, Olga Maria Silverio (São Paulo Medical Journal, 2003)
CONTEXT: There are few longitudinal studies that analyze the growth and nutritional status parameters of children born prematurely. OBJECTIVE: To evaluate the growth and dietary intake of preterm newborns in the first year of gestation-corrected age. DESIGN: Prospective clinical study. SETTING: Tertiary care hospital. PATIENTS: 19 children (7 male) who were born prematurely, with birth weight between 1000g and 2000g, which was adequate for the gestational age. PROCEDURES: At 3, 6, 9 and 12 months of gestation-corrected age, children were evaluated in relation to weight, height and cephalic perimeter, using the National Center for Health Statistics as the standard reference, and the Rozalez-Lopez and Frisancho standards for brachial perimeter and triceps and subscapular skinfolds. The calculated dietary intake was compared to the Recommended Dietary Allowances. MAIN MEASUREMENTS: The Z score was calculated for the weight/age, height/age and weight/height relationships, and the percentiles of the perimeters and skinfolds were considered. Dietary intake records were made using the 24-hour Dietary Recall and the Food Frequency Intake Questionnaire methods. The Virtual Nutri software was used to calculate energy and protein intake. RESULTS: The weight/age, height/age and weight/ height relationships and the brachial perimeter and triceps skinfold were statistically greater in the first semester in relation to the second. The cephalic perimeter remained above the 50th percentile for the ages studied and there was no difference in the subscapular skinfold between the first and second semesters, remaining below the 50th percentile. The calorie and protein intake, although statistically lower in the first than in the second semester, always remained above the recommended. CONCLUSIONS: The pace of growth is greater in the first semester than in the second, not reaching the standard expected for full-term newborns, with the exception of the cephalic perimeter, which remains adequate. Calorie/protein intake shows an inverse relationship with growth speed, remaining above the recommended for full-term newborns, although with difficulty in depositing subcutaneous fat, in spite of the high caloric intake.